Science—policy engagement to achieve “water for society—including all”. Editorial - Donoso, G.; Barron, Jennie; Uhlenbrook, Stefan; Hussein, H.; Choi, G. (MDPI, 2021)
After more than three years of implementing the 2030 Agenda for Sustainable Development, the 2019 World Water Week in Stockholm chose to focus on inclusiveness with the theme “Water for society—Including all” [...]